2011
DOI: 10.1038/nprot.2011.370
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule recognition force spectroscopy of transmembrane transporters on living cells

Abstract: Atomic force microscopy (AFM) has proven to be a powerful tool in biological sciences. Its particular advantage over other high-resolution methods commonly used is that biomolecules can be investigated not only under physiological conditions but also while they perform their biological functions. Single-molecule force spectroscopy with AFM tip-modification techniques can provide insight into intermolecular forces between individual ligand-receptor pairs of biological systems. Here we present protocols for forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Using this method, researchers have shown that the specificities of E-and N-cadherins are distinct ( preferring homophilic bonds), alongside producing different adhesive and compliant bonding forces. Similarly, ligand binding to atomic force microscope tips allows for examination of specific cellular molecules and their interactions [162]. Recently, biotin/streptavidin functionalization has shown that tension regulates actin depolymerization [163].…”
Section: Modified Cantileversmentioning
confidence: 99%
“…Using this method, researchers have shown that the specificities of E-and N-cadherins are distinct ( preferring homophilic bonds), alongside producing different adhesive and compliant bonding forces. Similarly, ligand binding to atomic force microscope tips allows for examination of specific cellular molecules and their interactions [162]. Recently, biotin/streptavidin functionalization has shown that tension regulates actin depolymerization [163].…”
Section: Modified Cantileversmentioning
confidence: 99%
“…The application of adhesion force mapping is an expanding fi eld where the power of the technique is limited by the stability and effectiveness of the functionalized probe. Procedures to functionalize probes require expertise across multiple disciplines; however, these techniques are now starting to become more standardized in practice (Heinisch J 2010, Puntheeranurak T 2011, allowing non-specialist AFM experimentalists to apply these adhesion mapping procedures to their research.…”
Section: Applicationmentioning
confidence: 99%
“…In the AFM measurement, the CD3ε CD -conjugated cantilever was firstly approached to PMSs and remained still at a constant force of 100 pN for 1 s to allow the protein-membrane interaction. Similar low contact forces have been widely used by the AFM community to study physiological systems with membranes to avoid disrupting membrane structures [59][60][61]. We analyzed the mechanical properties of PMSs by fitting the contact region in the approaching trace using the Hertz model (Supplementary information, Figure S1B).…”
Section: Closed-to-open Conformational Transition Of Cd3ε Cytoplasmicmentioning
confidence: 99%